2021
DOI: 10.1128/spectrum.00009-21
|View full text |Cite
|
Sign up to set email alerts
|

EPSP Synthase-Depleted Cells Are Aromatic Amino Acid Auxotrophs in Mycobacterium smegmatis

Abstract: We found that cells from Mycobacterium smegmatis , a model organism safer and easier to study than the disease-causing mycobacterial species, when depleted of an enzyme from the shikimate pathway, are auxotrophic for the three aromatic amino acids (AroAAs) that serve as building blocks of cellular proteins: l- tryptophan, l -phenylalanine, and l -tyrosine. That supplementation with only AroAAs is sufficient to rescu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…The amino acid intake can be partly explained by the fact that M. tuberculosis has an aroP2 homologue, an aromatic amino acid transporter ( 20 ). A comparable result was observed by the silencing of the aroA gene in M. smegmatis ( 21 ). This gene encodes the enzyme 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS), the sixth enzyme of the shikimate pathway.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The amino acid intake can be partly explained by the fact that M. tuberculosis has an aroP2 homologue, an aromatic amino acid transporter ( 20 ). A comparable result was observed by the silencing of the aroA gene in M. smegmatis ( 21 ). This gene encodes the enzyme 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS), the sixth enzyme of the shikimate pathway.…”
Section: Discussionsupporting
confidence: 80%
“…The aroA silencing provoked an impairment of bacterial growth within 24 h, suggesting that the abrupt reduction in endogenous levels of the EPSPS enzyme does not cause bacterial death, but impairs growth. However, supplementation with only the three amino acids l -tryptophan, l -phenylalanine, and l -tyrosine was sufficient to rescue the growth in aroA -knockdown cells, implicating that aroA from M. smegmatis is essential only when sufficient amounts of l -tryptophan, l -phenylalanine, and l -tyrosine (AroAAs) are not available ( 21 ). On knockout studies with the shikimate kinase-encoding aroK gene from M. tuberculosis , it was demonstrated that the essentiality of the mycobacterial shikimate pathway cannot be circumvented by supplementation with aromatic compounds, such as amino acids, p-hydroxybenzoate, p-amino-benzoic acid, and 2,3-dihydroxybenzoate ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The last two steps of the shikimate pathway are catalyzed by 5-enolpyruvylshikimate-3-phosphate synthase (EPSP) and chorismate mutase. Even though genetic studies have assessed their vulnerability as drug targets and crystal structures could aid in the design of structure-based inhibitors [ 28 , 29 ], to date, the development of inhibitors is still in its infancy [ 30 , 31 ].…”
Section: Inhibitors Of Amino Acid Biosynthesismentioning
confidence: 99%